Cytomorphological Study of Palpable Soft Tissue Tumors by Fine Needle Aspiration Cytology - Dwivedi, Mamta; Rani, Deepa; Tripathi, Anjani Kumar; Sirohi, Rohan; Gupta, Atul; Singh, Aradhana (Annals of Pathology and Laboratory Medicine, 2019)
Background: Soft tissue tumors are a highly heterogeneous group of tumors that are classified by the line of differentiation, according to the adult tissue they resemble. Objective of this study was to assess the utility of fine needle aspiration cytology (FNAC) in diagnosing soft tissue tumors and to do the histo-pathological correlation wherever possible. Methods: Conventional May-Grunwald Giemsa (MGG) staining was done in all the 100 cases and cytodiagnosis was rendered. Histopathology was available in 41 cases. The cytological diagnosis was correlated with histology in these cases. The accuracy rate, sensitivity, specificity, the positive and negative predictive value were calculated. P value was found by applying Fisher’s exact test. Results: The study was carried out on aspirates of 100 patients. Out of which 65 cases were benign, 30 were malignant while 5 cases were inadequate. Lipoma was the most common cytologically diagnosed benign lesion. Dermatofibrosarcoma protuberans (DFSP) and synovial sarcoma were found to be the most common malignant soft tissue tumors. Cyto-histological correlation could be achieved in 41 cases, with an accuracy of 92.7%. Conclusion: FNAC is a well-tolerated and cost-effective procedure. It provides predictive diagnosis of benign or malignant soft tissue tumors and also specific tumor type, especially after correlation with clinical and radiological findings.